Development parameters of the latent period as a response of rubber tree resistance to south smerican leaf blight - Zago Bevenuto, João Alberto [UNESP]; De Souza Passos, José Raimundo [UNESP]; Furtado, Edson Luiz [UNESP] (FapUNIFESP (SciELO), 2021)
The major phytosanitary problem for rubber tree cultivation in Brazil is the disease known as South American leaf blight, caused by the fungus Microcyclus ulei. Its symptoms manifest in young leaves and cause intense defoliation, resulting in reduced latex production and even the death of susceptible plants. Thus, this disease consists in a constant threat to East Asian plantations. As worldwide traditional breeding programs have evolved, interspecific hybrid clones have currently been used for planting. They are more productive and show better resistance to pathogens. However, traditional breeding programs have not led to significant progress in resistance to South American leaf blight since the selection is directed to clones with complete resistance. In this pathosystem, horizontal or partial resistance (HR) and vertical or complete resistance (VR) can act simultaneously, evidencing their complexity and difficult quantification. This study aimed to: Characterize the foliar lesion type in Hevea sp. X M. ulei pathosystem; verify the clonal susceptibility to pathogens; analyze the infection frequency for resistance quantification in Hevea sp. x M. ulei pathosystem, and recommend differentiating rubber tree clones to quantify M. ulei races in Brazil. The monocyclic parameters (latent period and lesion diameter) are applicable for resistance quantification in Hevea sp. x M. ulei pathosystem. Latent period had slight variation among clones. Lesion diameter had wide variation among clones and was a discriminating parameter for horizontal resistance and vertical resistance.
Parâmetros do desenvolvimento do período latente em resposta à resistência da seringueira ao mal das folhas
Keywords: Epidemiological modeling; Hevea sp; Horizontal resistance; Latent period; Microcyclus ulei; Vertical resistance